EFEKTIVITAS MEDIA PROMOSI KARTU KWARTET DENGAN SLIDE TERHADAP PENGETAHUAN DAN SIKAP SISWA SEKOLAH DASAR TENTANG PERILAKU HIDUP BERSIH SEHAT DI KECAMATAN DEPOK SLEMAN - , SAVIRA EVI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Elementary students are a very sensitive group to accept the change, because they were in early stages of growth and development. At this stage, they are easily guided, directed, and instilled good habits. The use of methods and media education should be appropriate and acceptable to the target. Objective: To determine the effectiveness of promotion media between quartet card to slide towards the knowledge and attitude of elementary school students. Methods: The study was a quasi experiment with using a pretest and posttest group design. This study was conducted in November 2012 until January 2013. The population in this study is the 4th grade students in Depok Sleman district. The sampling technique used in this study is purposive simple random sampling. The data were taken using a questionnaire given to respondents who meet the criteria. The data were analyzed with descriptive statistical techniques and analytical techniques of parametric t-test. Results: The effectiveness of quartet card health promotion media to increase knowledge of clean and healthy behavior on elementary students in Depok Sleman district, amounted to 27.53%